Sistem Pengolahan Dan Pemasaran Kerupuk Emping Melinjo Di BUMDes Desa Selubuk Kecamatan Air Napal Bengkulu Utara - Agustina, Mia Tri; sari, serly mayang; permana, ardi indra (Universitas Dehasen Bengkulu, 2023)
Melinjo plant or Gnetum gnemon is a shrub plant that grows well in tropical regions such as Indonesia, Malaysia, Thailand and the Philippines. This plant has a sturdy stem and large leaves and seeds that are shaped like beans. In Indonesia, each region has its own name for this melinjo plant, namely belinjo, melinjo, baguk, bagor, trangkil, and tangkil sako. Marketing means all efforts or business activities in delivering goods or services of producers to consumers, where these activities are aimed at satisfying needs and desires in a certain way called exchange.